Longitudinal analysis of aerobic performance indicators in elite cross-country skiers: Age- and sex-dependent trajectories across the career - Bucher, E.; Wehrlin, J. P.; Millet, G. P.; Steiner, T. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Elite cross-country (XC) skiers undergo standardized testing to monitor their performance development and to calibrate training prescriptions. However, the long-term progression of relevant performance indicators, such as maximal oxygen uptake (VO2max), performance at the second lactate threshold (LT2), and time-trial performance over an athlete's career remains unclear, with previous research focusing on the junior to U23 level [1]. This study aimed to investigate the longitudinal data from > 15 years of exercise testing with the Swiss XC ski national team to examine the trajectory of key performance indicators across the careers of male and female skiers.